(untitled) (LACCEI, 2024)
This work is developed with the objective of making an overview of existing publications on digital teaching competence, with the addition of establishing and identifying the existing conceptual frameworks in such a way that we can later carry out a measurement of the digital competence of the Peruvian teacher.. The search for published articles began, considering criteria such as: maximum six years of seniority, review in indexed databases and magazines related to education, keywords related to digital teaching competence, articles in Spanish and English, publications in English and Spanish, Publications in Latin America and Europe. Then we proceeded to analyze and evaluate with an adaptation of the prism methodology, reviewing whether the articles that contained information related to the select topic. After detailing the existing digital competition frameworks in Europe, it was found that some have also been applied in Latin America. Although we find that there are still countries such as Peru that still does not have an approved frame of reference that allows the development of digital skills of teachers and that above all allows to know the baseline that allows subsequently elaborating a plan for the development of the Teaching digital competence oriented to close existing gaps and create a relevant and contextualized training offer to Peruvian reality. This systematic review is carried out as part of a doctoral thesis.